The mediating role of job satisfaction in the effect of green transformational leadership on intention to leave the job - Oktaysoy, Onur; Topcuoglu, Ethem; Ozgen-Cigdemli, Asli Ozge; Kaygin, Erdogan; Kosa, Gozde; Turan-Torun, Burcu; Kobanoglu, Mehmet Selman; Uygungil-Erdogan, Selen (Frontiers in Psychology, 2025)
IntroductionThe literature on leadership has evolved in accordance with changing global expectations over time and the significance of new leadership approaches which are based on environmental sustainability has increased day by day. Green transformational leaders, one of the results of this evolution, are different from other leadership approaches in terms of their role in motivating employees and increasing their environmental awareness by integrating their environmental sensitivities into the organizational culture.MethodsThis study, which aims to determine the mediating role of job satisfaction in the effect of green transformational leadership on intention to leave, was conducted with 391 people working in 4 and 5 star hotels in Antalya region. Data obtained by convenience sampling method was examined with Smart-PLS program. The study was shaped on the axis of structural equation modeling.ResultsThe findings showed that green transformational leadership has a negative effect on intention to leave and job satisfaction plays a mediating role in this relationship. In addition, green transformational leaders were found to increase employees’ job satisfaction, strengthen their commitment to the organization and reduce intention to leave.DiscussionThe study shows that green transformational leadership has an effective structure not only in terms of green and environmental concepts but also in terms of organizational behavior. According to the Social Exchange Theory, green transformational leadership is thought to shape the job satisfaction of employees by interacting with them in accordance with moral and organizational norms.